2015
DOI: 10.2139/ssrn.2688989
|View full text |Cite
|
Sign up to set email alerts
|

Emission Reduction and Profit-Neutral Permit Allocations

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…41 "Polluter bailouts and lobbying during Covid-19 pandemic", The Guardian, April 17, 2020. 42 Burkey and Durden (1998) and Joskow and Schmalensee (1998) have detailed how firms can influence the regulator's decisions in the context of pollution rights markets, while Bovenberg and Goulder (2001), Hepburn et al (2013) and Nicolaï (2019) have shown that few permits are sufficient to neutralize the losses in profits and make the implementation of pollution permits acceptable. 43 On March 16, the Czech Prime Minister, Andrej Babis said that the European Green Deal should be put to one side.…”
Section: Acceptability Of Environmental Policiesmentioning
confidence: 99%
“…41 "Polluter bailouts and lobbying during Covid-19 pandemic", The Guardian, April 17, 2020. 42 Burkey and Durden (1998) and Joskow and Schmalensee (1998) have detailed how firms can influence the regulator's decisions in the context of pollution rights markets, while Bovenberg and Goulder (2001), Hepburn et al (2013) and Nicolaï (2019) have shown that few permits are sufficient to neutralize the losses in profits and make the implementation of pollution permits acceptable. 43 On March 16, the Czech Prime Minister, Andrej Babis said that the European Green Deal should be put to one side.…”
Section: Acceptability Of Environmental Policiesmentioning
confidence: 99%
“…Nicolaï (2015) discusses the importance of firms supporting the environmental policy. In our approach, the payments the firms make are used to reduce their costs in the future, which make it likely that a Tech Treaty will gain their support.4 Bretschger et al (2015) show that carbon-pricing policies should be complemented by R&D policy and discuss the importance of making technology diffusion part of R&D policy.…”
mentioning
confidence: 99%